Bad Environmentalism: Irony and Irreverence in the Ecological Age, Nicole Seymour (2018). (1st March 2020) - Fuchs, Susanne
Bad Environmentalism: Irony and Irreverence in the Ecological Age, Nicole Seymour (2018)Minneapolis and London: University of Minnesota Press, 320 pp., ISBN 978-1-51790-389-3, p/bk, 26.95ISBN 978-1-51790-388-6, h/bk, 108.00